2019
DOI: 10.1590/1413-785220192702205665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sagittal Balance Differences on Spondylolisthesis

Abstract: Objectives: This study aimed to compare the lumbar lordosis (LL) and spinopelvic parameters of patients with stage 1–2 spondylolisthesis to those of the normal population and demonstrate the importance of these parameters in sagittal balance. Methods: The lumbosacral parameters on the lateral radiographs of a total of 125 patients were retrospectively compared. Lumbosacral parameters including pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), lumbar lordosis angle (LLA), L5 incidence (L5I), L5 slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Multiple research works analyzed the correlation of LLA and PI suggesting a significant positive relationship of r = 0.40 to 0.72 (p < 0.001). 4,9,12,27 This showed that as the PI decreases, lumbar lordosis decreases and disc pressure increases and degeneration occurs in the disc leading to low back pain. In this study, we also found a positive significant correlation of r = 0.492 having a pvalue < 0.001 between PI and LLA.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple research works analyzed the correlation of LLA and PI suggesting a significant positive relationship of r = 0.40 to 0.72 (p < 0.001). 4,9,12,27 This showed that as the PI decreases, lumbar lordosis decreases and disc pressure increases and degeneration occurs in the disc leading to low back pain. In this study, we also found a positive significant correlation of r = 0.492 having a pvalue < 0.001 between PI and LLA.…”
Section: Discussionmentioning
confidence: 99%
“…In people with spondylolisthesis, changes are observed in the SS, PI and PT angles as the pelvic positions change. It is thought that the increase in SS, PI and PT angles leads to the progression of spondylolisthesis and many spinal problems [24]. People with L5-S1 spondylolisthesis have an increased SS angle, which affects the progression of spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a large PI is accompanied by a small STA, and a small PI was associated with a large STA [ 11 ]. Previous investigations have demonstrated that patients with large STA were more susceptible to lumbar disc herniation, whereas patients with small STA were prone to lumbar degenerative spondylolisthesis [ 20 , 21 ]. Ergun had also reported that the degree and risk of intervertebral disc degeneration and herniation increases in parallel to the increase of STA in the case of the same PI [ 22 ].…”
Section: Discussionmentioning
confidence: 99%